Lehrer*innenbildung und Bologna-Prozess Politische Strategien zur Einführung der Bachelor- und Masterabschlüsse im Bundesländervergleich - Schmees, Johannes Karl (Studien zur Professionsforschung und Lehrerbildung, 2020)
Contrary to the assumption of worldwide diffusion processes of internationally circulating reform ideas in education there are examples of regions that resist. In the present study, the phenomenon of incorporating international reform ideas into local education systems is examined using new institutionalism as a theory for its explanatory power of worldwide diffusion processes in education together with a set of cases that offer semi-lab-like conditions: Not all German federated states have adopted Bachelor's and Master's degrees for teacher training; some have maintained the state examination. Based on this empirical finding, the question of the dissertation is: Whether and how were the Bachelor's and Master's degree in German teacher training implemented on the federated statelevel in the period between 1999 and 2013? It can be shown that the federal ministers of higher education specified three core characteristics of the Bologna Process, namely the introduction of Bachelor's and Master's degrees, a credit point system, and modularisation. A decision of the Standing Conference of the Ministers of Education and Cultural Affairs of Germany made in 2005 further ensured that the reformed degrees were recognised nationwide for teachers as well. The educational organisations' demands were characterised by a large number of positive and only a few negative votes concerning the implementation of the Bologna Process in German teacher education. To provide specific insights into the reform process, this study focuses on teacher training for secondary school teachers, comparing the teacher training regulations as of 1999 with all subsequent changes until 2013 to obtain the degree of change for each federated state. As a result, it can be stated that eight states introduced reformed degrees into secondary school teacher education and eight states kept the state examination. Both groups are then compared as to whether a change of the degree towards Bachelor's and Master's is more likely to be accompanied by further reforms. The results suggest that while changes have occurred in all states, the percentage increase of courses in education and didactics, as well as the increased study duration, correlates positively with a change of the degree structure. Therefore one can interpret that the Bologna reforms, especially those concerning the degree structure, were used to implement other curricular and structural reforms that were not related to the Bologna Process itself. In the last step, plenary debates on the federated state level regarding the introduction of these Bologna reforms are analysed to examine the justifications for the introduction of a change in the degree structure, as well as for maintaining the state examination. Justifications or strategies for preserving the state examination are particularly relevant because they act against the political and public expectations analysed earlier. In a nutshell, it can be stated that the innovative strength of the partial reforms adopted in the hybrid model and the exclusion of a fundamental criticism of Bachelor's and Master's degrees are used as a strategy to reject the implementation of a new degree structure without being interpreted as non-innovative. Federated states that implemented the degree reform referenced decisions made in other states or regions, as well as possible negative consequences of not implementing the degrees, to support their decision while also presenting it within the discourse as a window of opportunity for more fundamental reforms in teacher training.